Benign juvenile focal epilepsy in a captive Iberian lynx (Lynx pardinus). Issue 4 (25th October 2019) - Mínguez, Juan J; Martinez, Fernando; Vargas, Astrid; Wessmann, Annette; Lorenzo, Valentina
Abstract : An 8‐week‐old intact male lynx cub ( Lynx pardinus ) from a captive breeding colony was presented with a 2‐day history of cluster seizures. There was no history of intoxication. Physical and neurological examinations were normal. Complete blood profile, infectious diseases panel, MRI of the brain and cerebrospinal fluid analysis were unremarkable. A diagnosis of suspected idiopathic epilepsy was made. The lynx cub was treated with increasing doses of phenobarbital and seizure activity stopped within 28 days. After 23 seizure‐free months, phenobarbital was tapered over 4 months and finally discontinued. No further seizures were observed during the follow‐up period of 8 years. Given the early onset followed by rapid and maintained remission, seizure semiology and the lack of underlying disease, a presumptive diagnosis of benign focal epilepsy similar to benign childhood focal epilepsies as described in human medicine is postulated.